Is There Really a Foreign Ownership Wage Premium? Evidence from Matched Employer-Employee Data - Fredrik Heyman; Patrik Gustavsson Tingvall; Fredrik Sjöholm (Research Institute of Industrial Economics (IFN), 2006)
Numerous studies on firm-level data have reported higher average wages in foreign-owned firms than in domestically-owned firms. This, however, does not necessarily imply that the individual workers wage increase with foreign ownership. Using detailed matched employer-employee data on the entire Swedish private sector, we examine the effect of foreign ownership on individual wages, controlling for individual and firm heterogeneity as well as for possible selection bias in foreign acquisitions. We distinguish between foreign greenfields and takeovers and compare foreign owned firms with both domestic multinationals and local firms. Our results show a considerably smaller wage premium in foreign owned firms than what has been found in studies conducted at a more aggregate level. Moreover, foreign takeovers of Swedish firms tend to have no or even a negative effect on wages.
Keywords: C23; F23; J31; 330; FDI; Foreign Ownership; Wages; Matched Employer-Employee Data; Propensity Score Matching; Direktinvestition; Multinationales Unternehmen; Lohnniveau; Schätzung; Schweden